There Will Be Rainbows: A Biography of Rufus Wainwright - Lake, Kirk (Itbooks, 2010)
"No contemporary pop performer's work mixes innovation and tradition like Rufus Wainwright's. He is the son of singer, songwriter, actor Loudon Wainwright III and legendary Canadian folk singer Kate McGarrigle whose story is one of towering highs and rock bottom lows in which family influences, sexual experimentation, and a crystal meth addiction in the early 2000s have greatly contributed."